1997
DOI: 10.1002/hep.510250302
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ursodeoxycholic Acid on Serum and Biliary Noncholesterol Sterols in Patients With Gallstones

Abstract: increase in cholesterol synthesis to maintain the body pool Litholytic bile acid ursodeoxycholic acid (UDCA) reof cholesterol unless the decrease in biliary cholesterol secreduces biliary cholesterol secretion and alters cholesterol tion is sufficient to compensate for reduced cholesterol abmetabolism by mechanisms that are not fully undersorption. However, the effect of UDCA on cholesterol metabostood. To evaluate cholesterol metabolism during UDCA lism, especially on cholesterol synthesis, has not been treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
4
2

Year Published

1998
1998
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
3
4
2
Order By: Relevance
“…After UDCA treatment, the concentrations of these sterols, as well as their ratios to cholesterol, increased significantly. The results are in agreement with those recently reported in patients with gallstones (16,17) and primary biliary cirrhosis (15). Miettinen et al (15)(16)(17) found a negative relationship between the change of the ratio of campesterol to cholesterol in serum before and during UDCA therapy and the change in cholesterol saturation in gallbladder bile.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…After UDCA treatment, the concentrations of these sterols, as well as their ratios to cholesterol, increased significantly. The results are in agreement with those recently reported in patients with gallstones (16,17) and primary biliary cirrhosis (15). Miettinen et al (15)(16)(17) found a negative relationship between the change of the ratio of campesterol to cholesterol in serum before and during UDCA therapy and the change in cholesterol saturation in gallbladder bile.…”
Section: Discussionsupporting
confidence: 93%
“…The results are in agreement with those recently reported in patients with gallstones (16,17) and primary biliary cirrhosis (15). Miettinen et al (15)(16)(17) found a negative relationship between the change of the ratio of campesterol to cholesterol in serum before and during UDCA therapy and the change in cholesterol saturation in gallbladder bile. From the results, the authors suggest that under these circumstances levels of plant sterols might be affected by their biliary elimination and therefore reflect changes in biliary cholesterol secretion.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations